A game of perceived risk in social commerce transactions – A suggestion for the integration of the trust (payment) feature on social commerce platform sales - PhamThi, VanAnh (Marketing & Menedzsment, 2022)
THE AIMS OF THE PAPER To decrease perceived risks and opportunism in social commerce transactions, many social media sites have integrated the checkout feature to their model of social media platform sales, which allows customers to immediately check out without being navigated to other websites. However, this feature is not agreeable to many merchants due to the uncontrollable customer data and other problems. Therefore, the purpose of the paper is to discuss whether merchants should set up the checkout feature in order to increase sales and decrease perceived risks as well as opportunism in social commerce or not. METHODOLOGY To pursue this purpose, the article adopts Prisoner’s Dilemma in game theory to analyze the game of perceived risk that relates to making the deal between sellers and buyers in two possibilities including (1) Do not set up checkout function in social commerce, and (2) set up the checkout function in social commerce. MOST IMPORTANT RESULTS The results show that opportunistic behaviors and perceived risk are the obstacles that negatively affect reciprocal trust, and deter the success of social commerce transactions. Therefore, the role of trusted intermediaries in s-commerce transactions is necesarry. As a result, integrating the checkout feature in s-commerce platforms is a better way to decrease perceived risk between buyers and sellers. Furthermore, it also facilitates removing the opportunistic behavior in social commerce and positively promotes the success of transactions. This study provides a new approach in research of trust and perceived risk in s-commerce. In particular, the paper applies game theory to address two possibilities of the role of s-commerce platforms in online transactions in order to mitigate perceived risk and opportunistic behaviors among buyers and sellers. RECOMMENDATIONS This study motivates online merchants will move to other services such as the checkout feature of these s-commerce platforms. It also convince other merchants to apply this feature when it is available. Further, the paper raises the attention of social network sites (SNS) providers to complete and upgate their features, which brings better user experience. More important, it promotes the development of social moral to make trust based on reciprocity become a kind of social custom.